2021
DOI: 10.1523/jneurosci.0223-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Transporter Is a Master Regulator of Dopaminergic Neural Network Connectivity

Abstract: Dopaminergic neurons of the substantia nigra pars compacta (SNC) and ventral tegmental area (VTA) exhibit spontaneous firing activity. The dopaminergic neurons in these regions have been shown to exhibit differential sensitivity to neuronal loss and psychostimulants targeting dopamine transporter. However, it remains unclear whether these regional differences scale beyond individual neuronal activity to regional neuronal networks. Here, we used live-cell calcium imaging to show that network connectivity greatl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 166 publications
0
13
0
Order By: Relevance
“…These observations confirm and expand literature findings demonstrating that ELS can alter the expression of such targets [ 11 ] and may suggest reduced DA synthesis and DAT-mediated responses to extracellular DA in VTA dopaminergic neurons from SS mice. There is growing appreciation of the key role played by the DAT in midbrain regions, which is not only limited to reducing extracellular dopamine levels, but also includes regulation of dopaminergic network connectivity and plasticity [ 43 , 60 , 61 ]. DAT is found in the plasma membrane of the perikaryal, axon terminal, and dendrites of SN and VTA dopamine neurons [ 55 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…These observations confirm and expand literature findings demonstrating that ELS can alter the expression of such targets [ 11 ] and may suggest reduced DA synthesis and DAT-mediated responses to extracellular DA in VTA dopaminergic neurons from SS mice. There is growing appreciation of the key role played by the DAT in midbrain regions, which is not only limited to reducing extracellular dopamine levels, but also includes regulation of dopaminergic network connectivity and plasticity [ 43 , 60 , 61 ]. DAT is found in the plasma membrane of the perikaryal, axon terminal, and dendrites of SN and VTA dopamine neurons [ 55 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The primary neuronal culture used in this study is derived from the ventral midbrain, which contains the dopaminergic nuclei SNc and VTA. Notably, it has been shown that SNc dopaminergic neurons are more sensitive than VTA dopaminergic neurons 22,23,[26][27][28][29][30][31]164 . Therefore, this model is likely to contain more VTA dopaminergic neurons than SNc dopaminergic neurons 22,[26][27][28][29][30][31] .…”
Section: Limitations To the Methodology And Model System Used In This Studymentioning
confidence: 99%
“…Following the entry into the neurons, METH increases intracellular calcium levels, alters the activity of kinases (Kantor and Gnegy, 1998;Khoshbouei et al, 2004;Foster et al, 2006;Goodwin et al, 2009;Xie and Miller, 2009;Lin et al, 2016), phosphatases (Foster et al, 2002(Foster et al, , 2006Elliott and Beveridge, 2005), or TAAR1 activity Miller, 2007, 2009) and stimulates the reverse transport of dopamine (dopamine efflux) through the dopamine transporter. METH-stimulated dopamine efflux leads to a rapid increase in extracellular dopamine levels in the brain (Mantle et al, 1976;Wall et al, 1995;Jones et al, 1999;Khoshbouei et al, 2003;Binda et al, 2005;Kahlig et al, 2005;Sulzer et al, 2005;Fog et al, 2006;Goodwin et al, 2009;Saha et al, 2014;Lin et al, 2016;Sambo et al, 2017;Miller et al, 2021). Additionally, METH interferes with the vesicular storage of dopamine in synaptic vesicles.…”
Section: Regulation Of Neurotransmissionmentioning
confidence: 99%
“…Future work in these areas and those that receive input from or send projections to the ventral midbrain will elucidate many of the collective population properties that predispose, give rise to addiction, or failures that lead to relapse. Furthermore, examination of brain regions and peripheral tissue types in acute ex vivo slice preparations, or cultures of cell types of interest, enable dissection of distinct intrinsic properties of these regions and how they are affected by METH without confounding of extrinsic brain region input or ascending sensory signals (Miller et al, 2019(Miller et al, , 2021.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation